2009
DOI: 10.1364/oe.17.012641
|View full text |Cite
|
Sign up to set email alerts
|

Frequency response and bandwidth enhancement in Ge/Si avalanche photodiodes with over 840GHz gain-bandwidth-product

Abstract: In this work we report a separate-absorption-charge-multiplication Ge/Si avalanche photodiode with an enhanced gain-bandwidth-product of 845 GHz at a wavelength of 1310 nm. The corresponding gain value is 65 and the electrical bandwidth is 13 GHz at an optical input power of -30 dBm. The unconventional high gain-bandwidth-product is investigated using device physical simulation and optical pulse response measurement. The analysis of the electric field distribution, electron and hole concentration and drift vel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…It can be seen that the GBP reaches a plateau at -5.8V (~100GHz), after which it further increases due to bandwidth enhancement as seen in Fig. 3(b), similar to what is reported in [16]. The 100GHz GBP is comparable to standard InPbased APDs [5].…”
Section: Small-signal Measurementssupporting
confidence: 82%
“…It can be seen that the GBP reaches a plateau at -5.8V (~100GHz), after which it further increases due to bandwidth enhancement as seen in Fig. 3(b), similar to what is reported in [16]. The 100GHz GBP is comparable to standard InPbased APDs [5].…”
Section: Small-signal Measurementssupporting
confidence: 82%
“…Figure 2 shows measured current-voltage characteristics of the fabricated CMOS-APD with and without optical illumination. The avalanche breakdown voltage can be defined as the voltage at which the dark current reaches 10 μA [6,7], and, with this definition, the avalanche breakdown voltage of the CMOS-APD is about 10.7 V. When the reverse bias voltage is small, the CMOS-APD has low photocurrents of about 0.5 μA. With the reverse bias voltage approaching the avalanche breakdown voltage, photocurrents start to increase dramatically with internal gain provided by the avalanche multiplication process.…”
Section: Measurement Results and Analysesmentioning
confidence: 99%
“…In order to realize CMOS EPICs for optical interconnects, implementation of high-speed and high-responsivity photodetectors is required. Germanium-based photodetectors have been investigated due to their large absorption coefficient at 1.3-μm and 1.5-μm wavelengths as well as compatibility with CMOS technology [6][7][8]. Another interesting approach is using standard CMOS technology without any modifications for 850-nm photodetector realization.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 illustrates that there is significant potential for increasing gain-bandwidth products by reducing k. Kang et al [23] exploited this approach, using a silicon multiplication region with k ~0.08 to achieve a record gain-bandwidth product limit for high bandwidth APDs, despite their APD having a much larger w than state-of-the-art III-V APDs. Further characterization of these devices by Zaoui et al [24] under higher biases showed that nonlocal effects can increase the bandwidth further; however under these conditions the leakage current rose to become orders of magnitude higher than the photocurrent. .…”
Section: Introductionmentioning
confidence: 98%